Cobalt oxide decorated zirconium oxide immobilized multiwalled carbon nanotubes as scaffolds for supercapacitors and the CO₂ reduction reaction - Yadav, Dharmendra Kumar (2022)
In the field of renewable energy research, the development of materials for use as highly efficient supercapacitors and designing electrocatalytic materials for the reduction of CO2 to produce useful chemicals are envisaged as two important sustainable routes. However, developing stable, selective, and efficient materials for these purposes is a highly challenging task requiring numerous design attempts. In this work, cobalt oxide decorated zirconium oxide immobilized multiwalled carbon nanotubes (MWCNTs-ZrO2-Co3O4) is reported as a catalyst and battery electrode material for the electrochemical reduction of CO2 and supercapacitor applications, respectively. The MWCNTs-ZrO2-Co3O4 electrode assembled for the supercapacitor shows a specific capacity of 258.9 C/g at a current density of 1.0 A/g. The MWCNTs-ZrO2-Co3O4 and activated carbon (AC) based asymmetric supercapacitor (MWCNTs-ZrO2-Co3O4//AC) displays specific energy in the range of 8.9 Wh/kg (at 837.2 W/kg) to 6.23 Wh/kg (at 1674.4 W/kg). The device, MWCNTs-ZrO2-Co3O4//AC displays high cycling stability with 97% capacity retention after 7000 cycles at a current density of 1.0 A/g. In the electrocatalytic reduction of CO2, the MWCNTs-ZrO2-Co3O4 scaffold produces selectively formic acid during the electrolysis at -1.1 V (vs. Ag/AgCl) in 0.1 M aqueous KCl solution. These results indicate that MWCNTs-ZrO2-Co3O4 can serve as a bifunctional material.